Italian cooking classic recipes and techniques - Mangolini, Mia; Chalkley, Julia; Mantovani, Francesca (Paris Flammarion, 2014)
This comprehensive introduction to Italian cooking features 250 step-by-step kitchen techniques, 130 authentic regional Italian recipes, and 8 video tutorials. Italian cuisine is one of life's great pleasures and Italian Cooking offers the step-by-step kitchen techniques that are the secret to success. An overview of fundamental cooking methods offers expertise in preparing antipasti, pizza dough, fresh and dried pasta, risotto, polenta, sauces, seafood, and ice cream.--
Includes index
13
Keywords: Cooking, Italian; Cooking, Italian; Cookbooks; Encyclopedias